A regulatory perspective of clinical trial applications for biological products with particular emphasis on Advanced Therapy Medicinal Products (ATMPs). (23rd July 2013) - Jones, David R.; McBlane, James W.; McNaughton, Graham; Rajakumaraswamy, Nishanthan; Wydenbach, Kirsty
<x xml:space="preserve">Abstract</x> The safety of trial subjects is the tenet that guides the regulatory assessment of a Clinical Trial Authorization application and applies equally to trials involving small molecules and those with biological/biotechnological products, including Advanced Therapy Medicinal Products. The objective of a regulator is to ensure that the potential risk faced by a trial subject is outweighed by the potential benefit to them from taking part in the trial. The focus of the application review is to assess whether risks have been identified and appropriate steps taken to alleviate these as much as possible. Other factors are also taken into account during a review, such as regulatory requirements, and emerging non‐clinical and clinical data from other trials on the same or similar products. This paper examines the regulatory review process of a Clinical Trial Authorization application from the perspectives of Quality, Non‐Clinical and Clinical Regulatory Assessors at the Medicines and Healthcare products Regulatory Agency. It should be noted that each perspective has highlighted specific issues from their individual competence and that these can be different between the disciplines.